Quality healthcare in extreme adversity: Developing a framework for action. (7th January 2020) - Leatherman, Sheila; Tawfik, Linda; Jaff, Dilshad; Jaworski, Grace; Neilson, Matthew; Letaief, Mondher; Syed, Shamsuzzoha Babar
Abstract: Quality issue : Improving quality of care has become a global health priority to improve health outcomes and strengthen health systems, particularly in the context of achieving universal health coverage. Initial assessment : The delivery of quality essential health services in settings of extreme adversity, such as fragile, conflict-affected, vulnerable or disaster contexts, has been identified as a high priority globally to address the massive level of need. Choice of solution : This paper provides an action framework to systematically address the quality of health services for state and non-state actors working in such settings. The framework is designed to be practical, comprehensible and simple in adoption and implementation. It describes challenges, a set of medical needs and population priorities, a menu of quality-related interventions, and a hierarchy of health system levels defining the roles and responsibilities of key actors. Conclusion: Optimizing the use of limited resources in delivering the best quality possible in 'the hardest of the hard settings' is imperative.